Higher School: Look Beyond the Horizon - Evgeniy N. Ivakhnenko; Leila I. Attaeva (Высшее образование в России)
The authors concentrate their attention on the problem of the future of Russian education in connection with the changes in the classifier of professions. The paper analyzes the prospects for Russian higher education in personnel training in the context of growing technological innovations. In this regard, attention is drawn to two aspects. The first aspect covers the question of how sensitive Russian higher school is to the existing and future changes in the requirements of the employer and the labor market, and in general to the training of graduates. The second aspect is an attempt to connect the impending deformations, social and humanitarian, of professional reproduction with the mission of higher education. The key question reads as follows: can a university change its mission towards solving the social task of overcoming the crisis of “unemployed young people” that is looming along with the growth of technological innovations and the robotization of labor?